Nguyên nhân và giải pháp hạn chế suy thoái tài nguyên nước lưu vực Sông Cái Phan Rang - Lan, Vũ Thị Thu; Sơn, Hoàng Thanh (Vietnam Journal of Earth Sciences, 2007)
The causes and solutions for mitigating degradation of water resources in the Cai Phan Rang river basin